The Conditions of the Mystical Experience by Pseudo-Dionysius the Areopagite. An Philosophical Attempt - MANIKOWSKI, MACIEJ (Filozofia Chrześcijańska, 2018)
Pseudo-Dionysius the Areopagita is one of the most interesting theologians and philosophers of the Middle Ages. He was, probably, a Christian neoplatonist, a Syrian monk, who lived and worked in a circle of the latest neoplatonist school, e.g. Proclus and/or Damascius. He was called the Father of Christian apophatic mystics. His concept of mystical experience shows two fundamental aspects. Pseudo-Dionysius points (and this is traditional to mystical experience), that this kind of experience starts from the purifi cation, and through the illumination, culminates in union with the First Principle. The mystical experience, in Pseudo-Dionysius also compatible with contemplation, is – on the one hand – triple movement of the soul (the straight, the circle, and the spiral) and – on the other hand – is the deifi cation of man, the union with God in His Energies, but not in His Essence. The deifi cation is the transformation of the human nature – he is still a human, a creation, but is transformed like – in patristic tradition – God became the man, so the man can become God, but only in deifi cation.